2020
DOI: 10.3389/fevo.2020.00051
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms Underlying Pupal Protective Color Switch in Papilio polytes Butterflies

Abstract: Mimicry is a survival strategy in which organisms deceive their predators by imitating other organisms or the surrounding environment. One example of this involves pupal color polymorphism, which is widely observed in butterflies and moths. It has been suggested that the pupal colors of Papilio butterflies are selected according to the tactile stimulation experienced before pupation (P). Specifically, larvae crawling on smooth leaves become green pupae, but those crawling on rough stems become brown pupae. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…Any variation in pupal colour plasticity in different zones also needs to be investigated. The molecular mechanism behind pupal colour dimorphism in P. polytes in Japan revealed that the brown colour was determined by melanin synthesis genes, tyrosine hydroxylase and laccase 2 genes while the green colour was determined by expression of both multiple bilin binding protein-related genes (blue pigmentation) and multiple juvenile hormone binding protein-related genes (yellow pigmentation) together (Yoda et al 2020). These genetic factors have not been studied in P. p. romulus in Sri Lanka previously or in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Any variation in pupal colour plasticity in different zones also needs to be investigated. The molecular mechanism behind pupal colour dimorphism in P. polytes in Japan revealed that the brown colour was determined by melanin synthesis genes, tyrosine hydroxylase and laccase 2 genes while the green colour was determined by expression of both multiple bilin binding protein-related genes (blue pigmentation) and multiple juvenile hormone binding protein-related genes (yellow pigmentation) together (Yoda et al 2020). These genetic factors have not been studied in P. p. romulus in Sri Lanka previously or in this study.…”
Section: Discussionmentioning
confidence: 99%
“…These supergenes have the potential to be coupled with life history-related traits ( Cain and Shepard 1954 ), resulting in significant variation of fitness between color morphs ( Abbott and Svensson 2005 ). Recent genomic work has revealed such supergenes associated with coloration during various life stages in several species, including those of the Heliconus and Papilio genera ( Joron et al 2011 , Kunte et al 2014 , Wellenreuther et al 2014 , Saenko et al 2019 , Yoda et al 2020 ). Furthermore, the different supergene complexes that have been found to control coloration at different life stages have also been found to be decoupled from each other ( Medina et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pigments, cuticular protein, and chitin are the main components of puparium (Futahashi et al, 2012;Liu et al, 2018;Yoda et al, 2020). So, we identified the genes related to these components.…”
Section: Genome-wide Identification and Expression Analysis Of Genes ...mentioning
confidence: 98%
“…Cuticle is mainly composed of chitin and many kinds of cuticular proteins (Liu et al, 2018). The pigment of green pupae was a mixture of blue (bile pigment) and yellow (carotenoids) chromoproteins (Ohnishi, 1959;Riley et al, 1984;Yoda et al, 2020), while melanin, canthaxanthine, papilioerythrin (oxidized lutein) were found in brown pupae (Ohnishi, 1959). Physiologically, ligatured abdomens experiment reveals that neuroendocrine mechanism involved in the pupal color dimorphism in Papilio xuthus (Awiti and Hidaka, 1982).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation